Temporary employment and work-life balance in Australia - Lass, Inga; Wooden, Mark (My University, 2020)
While it is often believed that temporary forms of employment, such as fixed-term contracts, casual work and temporary agency work, provide workers with more flexibility to balance work and private commitments, convincing empirical evidence on this issue is still scarce. This paper investigates the association between temporary employment and work-life balance in Australia, using longitudinal data from the Household, Income and Labour Dynamics in Australia Survey for the period 2001 to 2017. In contrast to previous studies, we compare results from pooled cross-sectional and fixed-effects regressions to investigate the role of time-constant unobserved worker characteristics in linking temporary employment and work-life outcomes. The results show that, after accounting for job characteristics and person-specific fixed-effects, among women only casual employment is unequivocally associated with better work-life outcomes than permanent employment. For men, we mostly find negative associations between all forms of temporary employment and work-life outcomes, but the magnitudes of these associations are much smaller and mostly insignificant in fixed-effects models. This result suggests that male temporary employees have stable unobserved traits that are connected to poorer work-life balance.
Journal of Family Research
Keywords: Families and relationships; Labour market